2007
DOI: 10.1016/j.jpainsymman.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Report of the Clinical Protocol Committee: Development of Randomized Trials for Malignant Bowel Obstruction

Abstract: Malignant bowel obstruction (MBO) is a commonly encountered palliative care problem. There have been very few comparative trials in this area, and consequently there is very little clinical evidence upon which therapy can be rationally based. The purpose of this paper is to highlight the discussion and decision-making process that was undertaken by the Clinical Protocol Subcommittee during the development of a proposed clinical trial of best medical care versus surgical or endoscopic treatment for MBO. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 28 publications
0
66
0
4
Order By: Relevance
“…A recent consensus conference defined malignant bowel obstruction (MBO) as a bowel obstruction beyond the ligament of Treitz that is either from an intra-abdominal primary cancer with incurable disease or from a non-intra-abdominal primary cancer with clear intra-peritoneal disease [1]. MBO occurs in up to 15% of patients admitted to palliative care wards and in 10-28% of patients diagnosed with colorectal cancer and management can be clinically challenging [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent consensus conference defined malignant bowel obstruction (MBO) as a bowel obstruction beyond the ligament of Treitz that is either from an intra-abdominal primary cancer with incurable disease or from a non-intra-abdominal primary cancer with clear intra-peritoneal disease [1]. MBO occurs in up to 15% of patients admitted to palliative care wards and in 10-28% of patients diagnosed with colorectal cancer and management can be clinically challenging [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, little highlevel evidence is available, with only one published randomized trial comparing emergency surgery and SEMS insertion followed by elective surgery [14]. Two protocols of randomized trials also have been published [15,16], but no results have been reported to date.…”
mentioning
confidence: 99%
“…As a result of a poor nutritional status and the multilevel obstructions found in malignant adhesive obstructive bowel patients, treatment is more complicated. Only 30-48.9% of the patients have been successfully treated, as mentioned in the literature (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%